ANALYSIS OF INNUDIATION PATTERN BASED ON DAM FAILURE AND FLOOD CASE STUDY IN SADAWARNA DAM SUBANG CITY - EKO WIDYANTO - NIM : 25014308, BAMBANG
Innudiation would possibly occur for two reasons. The first is because of the flood and the second may be due to the collapse of the dam that impacts the influx of water on the downstream of the dam. Sadawarna dam is a dam located in the village of Sadawarna, Kabupaten Subang. The dam is the soil dam type that comes with a capacity of 49 million cubic meters with an elevation of 80 above mean sea level and top of dam at 82 above mean sea level. Sadawarna dam has 32 thousand km2 waterhseds. As the other damsÃ‚Â’ characteristics, Sadawarna dam has a vulnerability to the dam break. This thesis examined the dam break vulnerability in two ways. Firstly, it utilized a modeled dam Sadawarna which experienced dambreak with a collapse mechanism arranged in HEC-RAS. While the second mechanism was by modeling the dam with HEC-RAS that obtained some flood data supplies due to the flood discharge dambreak from HEC-HMS. The aforementioned HEC-RAS modeling was divided into three mechanisms, namely the time of dam overtopping experience, the piping at the top of the dam experience, and the piping at the bottom of the dam experience. Based on testcase that conducted in HEC-RAS through partial dambreak test case, the results obtained relative to be doubt. Meanwhile with use dam break debit from HEC-HMS as the flood debit, the result is more convincing refers to previous research. In this conducted research, the used water resources depended on the respective methods of modeling. On the model which purely used HEC-RAS, the debit data were not included into a boundary condition, but rather into the connection that connected between the puddled and inundated areas. While on the model supported by HEC-HMS, it utilized the flood discharge data from the HEC-HMS in order to be included into the boundary condition on the HEC-RAS. The research results indicated that overtopping mechanism had a greater impact than the other two mechanisms. Based on the results of modeling using Hec-RAS 5.0.3, it was obtained that 18 villages are included into high dangerous zones, 9 villages are included into medium dangerous zones and 26 villages are included into low dangerous zone.